«Emakume-bahitzea» eta lege fonetikoak Georg von der Gabelentzen «Hizkuntza arrotzak jasotzeko eskuliburua»-ren ingurukoak - Hurch, Bernhard (Anuario del Seminario de Filología Vasca "Julio de Urquijo", 2009)
In his late years Georg von der Gabelentz publishes a Handbook for collecting data from foreign languages. In his legacy we found one test-copy filled in by himself for Basque. As I show this handbook does not seriously reflect the state of data collection in his time and it literally reproduces word lists already used in his earlier publication on Basque and Berber. Also the Basque version already includes parallel word forms from Tuareg and Kabyl. Schuchardt, when reviewing the v.d. Gabelentz' Basque and Berber works, severely criticizes the sloppy methodological basis as well as the lack of knowledge of the relevant literature. The public and private discussion of the two scholars is documented in this contribution. V.d. Gabelentz at one point responds to Schuchardt's methodological criticism by mentioning that peoples which lack continuity in societal development may not be expected to present continuity in higher intellectual developments like regular sound changes.